2020
DOI: 10.1038/s41467-020-16077-z
|View full text |Cite
|
Sign up to set email alerts
|

Red-phosphorus-impregnated carbon nanofibers for sodium-ion batteries and liquefaction of red phosphorus

Abstract: Red phosphorus offers a high theoretical sodium capacity and has been considered as a candidate anode for sodium-ion batteries. Similar to silicon anodes for lithium-ion batteries, the electrochemical performance of red phosphorus is plagued by the large volume variation upon sodiation. Here we perform in situ transmission electron microscopy analysis of the synthesized red-phosphorus-impregnated carbon nanofibers with the corresponding chemo-mechanical simulation, revealing that, the sodiated red phosphorus b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
76
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 96 publications
(80 citation statements)
references
References 46 publications
3
76
0
1
Order By: Relevance
“…Compositing phosphorus with carbon materials can avoid the unexpected side reactions of the red P anode, achieving excellent long‐term cycling lifespans. [ 139 ]…”
Section: The Electrochemical Performance Of Heterostructuresmentioning
confidence: 99%
“…Compositing phosphorus with carbon materials can avoid the unexpected side reactions of the red P anode, achieving excellent long‐term cycling lifespans. [ 139 ]…”
Section: The Electrochemical Performance Of Heterostructuresmentioning
confidence: 99%
“…[11][12][13][14] To simultaneously guarantee good Li + transport kinetics and endurable cycling life, the design of battery electrode materials should balance structural/crystalline integrity with particle size/surface area. [15][16][17][18][19][20][21] Ideally, the electrode material should have a sufficiently large specific surface area (that is, the dimensions is small) and the particles should be tightly integrated to ensure the stability of the overall structure of the electrode. In this sense, mesocrystalline materials have been targeted as a good candidate.…”
mentioning
confidence: 99%
“…Recently, Zhou et al prepared a RP‐impregnated carbon nanofiber composite (P@CNF) and investigated its sodiation process and capacity fading mechanism through an in situ TEM technique and chemo‐mechanical simulation (Figure 6e–g). [ 17 ] They found that RP particles would be softened in the alloying process, which showed excellent malleability. Furthermore, the main reason for the capacity decay of RP could be attributed to the side reactions that occurred during the sodiation process in which the extremely reactive sodiated phosphorus compounds would form.…”
Section: Anodes For Sibsmentioning
confidence: 99%
“…[ 14,16 ] In addition, in situ characterizations techniques, such as in situ transmission electron microscopy (TEM), have been increasingly used to study the reaction between Na + and anode materials, which could let us take a closer look at how Na + are stored and further improve the properties of sodium storage. [ 17 ] Most important of all, there is no specific review to focus on the anode materials for SDIBs. Although SDIB is a newly developing battery system that emerged in the past 5 years, it shows a good application prospect due to its high energy density and low cost.…”
Section: Introductionmentioning
confidence: 99%